2007
DOI: 10.1529/biophysj.106.101485
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Amyloid-β Aggregation with Fiber-Based Fluorescence Correlation Spectroscopy

Abstract: Soluble aggregates critically influence the chemical and biological aspects of amyloid protein aggregation, but their population is difficult to measure, especially in vivo. We take an optical fiber-based fluorescence correlation spectroscopy (FCS) approach to characterize a solution of aggregating amyloid-beta molecules. We find that this technique can easily resolve aggregate particles of size 100 nm or greater in vitro, and the size distribution of these particles agrees well with that obtained by conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…FCS, in different forms, has proved to be an effective tool for following the size of evolving protein aggregates (32)(33)(34). 100 M of both peptides (at 1000:1 unlabeled:tetramethylrhodamine-labeled peptide ratio) were incubated for 6 h under physiological buffer conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FCS, in different forms, has proved to be an effective tool for following the size of evolving protein aggregates (32)(33)(34). 100 M of both peptides (at 1000:1 unlabeled:tetramethylrhodamine-labeled peptide ratio) were incubated for 6 h under physiological buffer conditions.…”
Section: Resultsmentioning
confidence: 99%
“…ssNMR studies were performed on aggregates of 7S ⌬G25 peptide containing isotopically enriched Val 18 , Phe 19 , Ala 21 , Gly 33 , and Leu 34 residues. These studies revealed that S ⌬G25 fibrils are also rich in ␤-sheet conformations, similar to the amyloid fibrils formed by S and full-length A␤ (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, the resolution and the sensitivity were poor due to the low numerical aperture (NA) of the single-mode fiber. While this is still useful for monitoring multiply-labeled objects such as protein aggregates, 5 the device is impractical for single molecule detection. In addition, the instrument still required alignment of the excitation laser into the fiber, and of the fluorescence signal into the small aperture of the typical avalanche photodiode detector.…”
Section: Introductionmentioning
confidence: 99%
“…The application of near-field optical probes for FCS measurements on cellular membranes is expected to provide a substantial advantage over the use of arrayed subwavelength apertures since one has the ability to image the cell surface at high spatial resolution [15][16][17], in order to identify areas of interest, prior to conducting FCS measurements on targeted areas of the membrane. Although FCS has been successfully reported using an untapered fiber optic probe [18], the use of fiber-based optical probes with nanometer-sized apertures has only recently been demonstrated in our laboratories [19]. This article reviews our recent advances toward fabrication of near-field optical probes for biological imaging [20] and our initial demonstration of the utility of these probes for FCS measurements in 2D membranes with subdiffraction-limited resolution [19].…”
Section: Introductionmentioning
confidence: 99%